Facile synthesis of graphene oxide-polyaniline-copper cobaltite (GO/PANI/CuCo2O4) hybrid nanocomposite for supercapacitor applications - Verma S.; Pandey V.K.; Verma B. (My University, 2025)
A novel type ternary GO/PANI/CuCo2O4 composite for electrode material was successfully synthesized and ensured by different characterizations such as XRD (X-ray diffraction), FTIR (Fourier transform infrared spectroscopy), FE-SEM (Field emission scanning electron microscopy), and EDS (Energy-dispersive X-ray spectroscopy). The interconnected morphology of ternary GO/PANI/CuCo2O4 indicates superior electrochemical performance. Ternary GO/PANI/CuCo2O4 displayed the maximum specific capacitance of 741.39 F/g at 1 mV/s scan rate and 312.72 F/g at 1 A/g current density using three-electrode and symmetric two-electrode system, respectively. The ternary GO/PANI/CuCo2O4 electrode based symmetric device had specific energy of 62.54 Wh/kg at 1 A/g current density and specific power of 5997.61 W/kg at 20 A/g. The systems have a wide potential window of 1.2 V, which is beneficial for the energy density. The ternary material electrode also has the lowest value of charge transfer resistance (Rct) as 12.23 Ω and relatively good specific capacitance of 84.25% after 5000 cycles. The excellent electrochemical nature of ternary GO/PANI/CuCo2O4 is mainly because of the synergistic effect which has brought this material to the spotlight for the supercapacitor application. © 2022 Elsevier B.V.